2013
DOI: 10.1371/journal.pone.0053234
|View full text |Cite
|
Sign up to set email alerts
|

Association between Common Variants near LBX1 and Adolescent Idiopathic Scoliosis Replicated in the Chinese Han Population

Abstract: BackgroundAdolescent idiopathic scoliosis (AIS) is one of the most common spinal deformities found in adolescent populations. Recently, a genome-wide association study (GWAS) in a Japanese population indicated that three single nucleotide polymorphisms (SNPs), rs11190870, rs625039 and rs11598564, all located near the LBX1 gene, may be associated with AIS susceptibility [1]. This study suggests a novel AIS predisposition candidate gene and supports the hypothesis that somatosensory functional disorders could co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 65 publications
1
43
0
1
Order By: Relevance
“…The variant rs11190870 seems to be associated to idiopathic scoliosis irrespective of scoliosis curve severity [28][29][30]. This is supported by our findings, where we found no substantial differences in OR between mild, moderate, or severe scoliosis compared with controls.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The variant rs11190870 seems to be associated to idiopathic scoliosis irrespective of scoliosis curve severity [28][29][30]. This is supported by our findings, where we found no substantial differences in OR between mild, moderate, or severe scoliosis compared with controls.…”
Section: Discussionsupporting
confidence: 88%
“…This association has subsequently been replicated in several North American and East Asian cohorts, suggesting the region on 10q24.31 harboring the LBX1 gene, to be a true susceptibility locus for idiopathic scoliosis [28][29][30]. In this study, we found a highly significant association of rs11190870 to idiopathic scoliosis also in a Scandinavian population, and as such, confirm the A1, allele 1 (risk allele); A2, allele 2; RAF, risk allele frequency; OR, odds ratio; CI, confidence interval; GPR126, G protein-coupled receptor; LBX1,ladybird homeobox 1; CHL1, cell adhesion molecule L1-like.…”
Section: Discussionmentioning
confidence: 80%
“…genotyped using the MassArray system (Sequenom, San Diego, California) with primers of c.886G> A (Fwd: 5prepared by the Beijing Genomics Institute (Shenzhen, China), as described previously(Buetow et al, 2001;Gao et al, 2013).…”
mentioning
confidence: 99%
“…Sequencing of positional candidate genes of a large family of Bulgarian descent revealed a missense mutation rs121434591 as a cause for vocal cord and pharyngeal weakness with distal myopathy (Senderek et al, 2009). rs11190870, an intergenic SNP located 6745 bp downstream of the Ladybird homeobox 1 gene (LBX1), is associated with adolescent idiopathic scoliosis (Chettier et al, 2015;Gao et al, 2013;Grauers et al, 2015;Jiang et al, 2013;Londono et al, 2014;Miyake et al, 2013;Takahashi et al, 2011).…”
Section: Polymorphisms In Uces Are Associated With Various Diseasesmentioning
confidence: 99%